2015
DOI: 10.1111/jzo.12307
|View full text |Cite
|
Sign up to set email alerts
|

Role of habitat heterogeneity and landscape connectivity in shaping gene flow and spatial population structure of a dominant rodent species in a tropical dry forest

Abstract: Evaluating how habitat heterogeneity and landscape connectivity influence finescale population processes of gene flow and spatial population structure is key for understanding animal dispersal. Liomys pictus is a heteromyid rodent that inhabits tropical dry deciduous and semideciduous forests, where it is a dominant, abundant species and a key element on the ecosystem as seed disperser. We evaluated how landscape features shaped the genetic structure and gene flow at a fine scale among L. pictus populations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 40 publications
1
18
0
1
Order By: Relevance
“…Most landscape genetics inference studies have assumed either a positive or negative linear relationship between landscape features and cost surfaces (Garroway, Bowman, & Wilson, 2011;Koen, Bowman, & Walpole, 2012), including examples with rodent populations (Chiappero et al, 2016;Howell et al, 2017;Mora et al, 2017;Ortiz et al, 2017), despite that nonlinear responses are expected to be more common (Marrotte & Bowman, 2017;. Here, we found nonlinear relationships relative to landscape resistance for both humidity and temperature, variables that influence genetic connectivity in different species like the northern quoll (Dasyurus hallucatus; Hohnen et al, 2016) and Liomys pictus (Garrido-Garduño et al, 2015). Temperature has been explicitly proposed as determinant for genetic connectivity in climate sensitive species, for example, the American pika (Ochotona princeps), a heat intolerant, and cool microclimate restricted species for which an increase in temperature adversely affects gene flow (Castillo, Epps, Davis, & Cushman, 2014).…”
Section: Environmental Features and Genetic Connectivitymentioning
confidence: 66%
See 2 more Smart Citations
“…Most landscape genetics inference studies have assumed either a positive or negative linear relationship between landscape features and cost surfaces (Garroway, Bowman, & Wilson, 2011;Koen, Bowman, & Walpole, 2012), including examples with rodent populations (Chiappero et al, 2016;Howell et al, 2017;Mora et al, 2017;Ortiz et al, 2017), despite that nonlinear responses are expected to be more common (Marrotte & Bowman, 2017;. Here, we found nonlinear relationships relative to landscape resistance for both humidity and temperature, variables that influence genetic connectivity in different species like the northern quoll (Dasyurus hallucatus; Hohnen et al, 2016) and Liomys pictus (Garrido-Garduño et al, 2015). Temperature has been explicitly proposed as determinant for genetic connectivity in climate sensitive species, for example, the American pika (Ochotona princeps), a heat intolerant, and cool microclimate restricted species for which an increase in temperature adversely affects gene flow (Castillo, Epps, Davis, & Cushman, 2014).…”
Section: Environmental Features and Genetic Connectivitymentioning
confidence: 66%
“…According to our expectations, we identified that vegetation (Russo et al, 2016). Another example showed that forested areas in a tropical dry forest function as corridors for dispersal for the spiny pocket mice Liomys pictus, overcoming the potential limiting effect of roads across the landscape (Garrido-Garduño et al, 2015); forests also facilitate gene flow in chipmunks (Tamias striatus) inhabiting fragmented landscapes like agroecosystems (Kierepka et al, 2016). Moreover, D. merriami activity peaks exhibit a behavior tightly associated with predator avoidance (Daly, Behrends, Wilson, & Jacobs, 1992;Soltz-Herman & Valone, 2000),…”
Section: Environmental Features and Genetic Connectivitymentioning
confidence: 75%
See 1 more Smart Citation
“…In our study, LCP and CT performed equally well with the exponential distribution, and it was not possible to resolve competing assumptions (e.g., single or multiple optimal paths). Circuit‐theory‐based analysis is commonly highlighted as more informative than LCP about gene flow (Coulon et al., ; Garrido‐Garduño, Téllez‐Valdés, Manel, & Vázquez‐Domínguez, ; La Point, Gallery, Wikelski, & Kays, ; McRae et al., ), but comparisons have seldom been made in urban landscapes. Urban landscape characteristics could lead to different relative performance between LCP and CT‐based models.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding rodents, Garrido‐Garduño et al . () studied the genetic structure of the Painted spiny pocket mouse Liomys pictus and found that populations were clustered according to clear landscape boundaries, mainly defined by precipitation and stream channels. Furthermore, Gerlach & Musolf () found the same pattern for the bank vole Clethrionomys glareolus , where rivers and highways acted as strong barriers to gene flow.…”
Section: Discussionmentioning
confidence: 99%